Quality Assessment of concrete utilizing treated waste water (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
concrete is the most extensively used construction material. Every year about 1.5 to 3 tonne/capita of concrete being produced using fresh water in developing countries. Approximately about 150 litres of portable water is required for producing 1m3 of concrete [1]. The present use of portable water for the preparation of concrete imposes a heavy burden on the cost of production, especially at places where there is high demand and shortage of supply of portable water for domestic consumption. Hence measures to be taken to conserve portable water as much as possible to prevent the shortage in the future. A practical solution would be the use of treated effluent from the wastewater treatment plant for concrete production, which will economically benefit the construction industries and conserve portable water.The suitability of using wastewater for mixing in concrete was experimentally studied by moulding the concrete cubes using tap water (TW), treated wastewater (TWW). From the results it was observed that standard consistency, setting time and strength of concrete are found to be satisfactory in compression strength.The average compressive strength was also being posh by the type of mixing water. It was found that the compressive strength of cubes obtained from TWW is almost same as that of TW. Hence, from this study it is concluded that treated wastewater (TWW) can be used in place of tap water for production of concrete. The environmental degradation can be reduced by using the treated effluent for concrete production and cost of the concrete can be reduced considerably. Hence, portable water can be conserved